Perceived stress and coping behavior among future nurses: A cross-sectional study in West Bengal, India - Dasgupta, Aparajita; Podder, Debayan; Paul, Bobby; Bandyopadhyay, Lina; Mandal, Shamita; Pal, Arkaprovo; Mandal, Moumita (Indian journal of community medicine, 2020)
Background: Demanding clinical and academic environments have been potential sources of stress among nursing students. Inability to cope effectively often potentiates this stress. If not intervened early, this may have a detrimental effect on health and may eventually affect the future workforce in rendering care. Objectives: The objective of this study was to explore the levels and sources of perceived stress and coping behavior among undergraduate nursing students in West Bengal. Materials and Methods: This descriptive cross-sectional study was conducted in two nursing training institutions in West Bengal, from July to September 2018, using a validated pretested self-administered questionnaire comprising demographics, Perceived Stress Scale (PSS), and coping behavior inventory (CBI). Students having at least 6 months of clinical exposure were invited to participate. Of 256 eligible students, 182 returned completed questionnaires, giving an overall response rate of 71%. Descriptive statistics, Pearson's correlation, and multiple regression analysis were performed using SPSS 16.0 software. Results: "Stress from assignments and workload" and "problem-solving" was the most prominent stressor and coping behavior (Factor rank 1) respectively among students. Statistically significant correlation was observed between overall mean PSS and CBI score (r = 0.306, P < 0.01). Years of education, self-decision to join, increased screen time, staying at hostel significantly predicted stress (R2 = 0.248, F = 9.640, P < 0.01), and coping behavior (R2 = 0.223, F = 10.077, P < 0.01) among students. Conclusions: Stress from academics and clinics were high among nursing students. As they are the future carers, it is apt to intervene early to mitigate their stress and enhance their coping skills during professional training and practice.